2020
DOI: 10.1038/s41398-020-0690-4
|View full text |Cite
|
Sign up to set email alerts
|

Do nonpharmacological interventions prevent cognitive decline? a systematic review and meta-analysis

Abstract: At present, prevention is particularly important when there is no effective treatment for cognitive decline. Since the adverse events of pharmacological interventions counterbalance the benefits, nonpharmacological approaches seem desirable to prevent cognitive decline. To our knowledge, no meta-analyses have been published on nonpharmacological interventions preventing cognitive decline. To investigate whether nonpharmacological interventions play a role in preventing cognitive decline among older people, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 86 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…In recent years, the potential usefulness of cognitive training in normal aging and MCI has received increased attention ( Brown, 2015 ; Vannini et al, 2017 ). Recent meta-analyses and reviews have reported that non-pharmacological cognitive interventions are effective in maintaining cognitive function in high-risk older adults ( Kidd, 2008 ; Li et al, 2011 , 2014 , 2017 ; Hong et al, 2015 ; Janoutova et al, 2015 ; Sherman et al, 2017 ; Yao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the potential usefulness of cognitive training in normal aging and MCI has received increased attention ( Brown, 2015 ; Vannini et al, 2017 ). Recent meta-analyses and reviews have reported that non-pharmacological cognitive interventions are effective in maintaining cognitive function in high-risk older adults ( Kidd, 2008 ; Li et al, 2011 , 2014 , 2017 ; Hong et al, 2015 ; Janoutova et al, 2015 ; Sherman et al, 2017 ; Yao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, cognitive training induced at least moderate improvement in cognitive test performance in both MCI and patients with mild to moderate AD, and this achievement was maintained over a short or medium period [13]. This method also prevented cognitive decline among older people at risk for dementia, in terms of reducing the incidence of MCI or dementia [47]. Reminiscence therapy encourages the discussion of past experiences, using materials such as photographs, books, old newspapers, and familiar items from the past [12], although some studies applied modern technology such as personalized digital memory book, mobile application, and a computer-aided programs [48] to evoke memories and facilitate sharing their experiences.…”
Section: Cognitive Interventionsmentioning
confidence: 96%
“…As the values brought by pharmacological therapies have demonstrated very limited and possible side effects, which sometimes counterbalance their benefits (Wilkinson et al, 2003;Kavirajan and Schneider, 2007), the demand for seeking evidence-based alternative interventions has transitioned gradually from being necessary to urgent. Additionally, many medical societies show a rising interest in how non-pharmacological interventions could help patients with dementia to maintain daily functional independence (Yao S. et al, 2020). Physical approaches such as acupuncture seem to be desirable for patients with cognitive disorders, especially for those who ask for long-term treatment (Su et al, 2020a).…”
Section: Applicability For Clinical Practicementioning
confidence: 99%